Two new trematodes from the intestine of a yellow bat, Nycticeius kuhlii from Lucknow, India - Agrawal, Vinod (Universidad de Costa Rica, 1967)
Se describen dos especies nuevas de tremátodos, parásitos intestinales del murciélago amarillo Nycticeius kuhlii: Prosthodendrium (Paralecithodendrium) thapari, y Anchitrema lucknowensis.